Explaining reurbanization: Empirical evidence of intraregional migration as a long-term mobility decision from Germany - Gesa Matthes (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Following the discussion on reurbanization (changing intra-regional migration patterns), our research project treats transport-related consequences of this spatial development in German city regions. The hypothesis is that reurbanization bears potential to spread environmentally friendly ways of organizing daily mobility - but that the chance of those positive effects might be given away, if policy does not accompany the process adequately. The aim of this project is to assess the current impact of reurbanization on passenger transport in city regions and to find further potential to reduce motorized passenger kilometres in order to deduce first planning approaches. This paper focuses on the question whether a household decides to move or to stay in its current dwelling and also analyses how the results vary in time and space. After having deduced factors on the decision to move, a logistic regression is run on the SOEP-data. The analysis shows that observed differences in time are mainly due to difference in behaviour regarding the factors number of employed persons and the event birth whereas spatial variation is mainly due to structural differences.
Keywords: O18; O21; R14; R21; 330; Relocation; move; migration; reurbanization; transport